Challenges in the execution of public health research: Reflections from Public Health Research Initiative (PHRI) grant management in India - Deepak Saxena; Poonam Trivedi; Ruchi Bhatt; Sandul Yasobant; Priya Bhavsar; Khushi Kansara; Farjana Memon; Dileep Mavalankar (Elsevier, 2022)
Background: Well-planned health research is fundamental to the success of any public health system in leading to better population health outcomes. Although the Indian public health system is unique, it lacks strong linkages between research and practice. There is a pressing need to address the gap in the research to reduce the disease burden in the country. Although various efforts are made to enhance public health research, such research is rarely documented as a process. The objective of the present paper is to document issues and challenges in managing public health research grants awarded to the PHRI fellows from 2013-to 2021 under the PHRI project. Method: A mixed-method approach, including qualitative (in-depth) interviews and secondary review, was adopted to collect the challenges in executing PHRI grants (during 2013-2021). The in-depth interviews were conducted among the PHRI execution team, whereas the secondary document review was conducted among the PHRI fellows, and the findings are documented under major themes like administrative, technical, and financial issues and/or challenges. Result: A total of 35 candidates 16 intramural (IM) candidates affiliated with PHFI or IIPH institutes and 19 extramural (EM) candidates affiliated to other academic institutes were selected for the fellowship, The common challenges identified amongst intra & extramural fellows were inability to disseminate the study findings, challenges in communication and getting audited statements, changes in study methods without prior permission, mid study attrition of CO-PIs and high budget utilization. The specific difficulties identified from extramural fellows were change in institute affiliation, lack of support to fund utilization from the parent institute and difficulties in field validation. Conclusion: The present perspective emphasizes that the management and implementation of a research grant is the crucial part of achieving a project's desired outcome. The learnings of PHRI grant execution allows the researchers to understand the issues in terms of methodological rigour and financial guidelines, rigorous tracking of the project activities, and complying with the terms of funding agreement are crucial. The challenges explored in this grant execution recommend developing a structured public health grant management leadership program for researchers and executors.